Transformational Management of Islamic Higher Education: A Case Study of A Nahdlatul Ulama Affiliated University in Enhancing Academic Quality and Global Competitiveness - Mispani Mispani; Agus Setiawan; Choirudin Choirudin; Aprezo Pardodi Maba; Rani Darmayanti; Samuel Karim; Subandi Subandi (Nazhruna: Jurnal Pendidikan Islam, 2026)
The transformation of Islamic higher education institutions in Indonesia has become increasingly urgent as newly established universities face growing pressures to achieve academic excellence, strengthen governance, and enhance global competitiveness while maintaining their religious and cultural identity. Despite this urgency, empirical studies examining how value-based transformational management operates in emerging Islamic universities remain limited, particularly within Nahdlatul Ulama (NU)-affiliated institutions, such as Universitas Ma’arif Lampung (UMALA). This study investigates transformational management practices at UMALA, a newly established Islamic university, by examining how strategic leadership, internal quality assurance, cultural integration, and international collaboration function as interrelated pillars of institutional transformation. Employing a qualitative case study approach, data were collected through in-depth interviews with university leaders and academic staff, document analysis of strategic plans, quality assurance reports, and cooperation agreements, as well as participant observation of institutional activities. The findings reveal that UMALA’s strategic leadership is deeply grounded in NU values of tawassuth (moderation), tasamuh (tolerance), and tawazun (balance), which shape participatory governance and ethical decision-making. The implementation of a digitally supported Internal Quality Assurance System (SPMI) has strengthened academic accountability, improved accreditation outcomes, and fostered a research-oriented culture. Cultural integration is systematically embedded in the curriculum and campus life, reinforcing institutional identity while supporting modernization. Furthermore, sustained national and international collaborations have expanded UMALA’s academic visibility and contributed to its regional and global engagement. This study highlights the need for developing context-sensitive, value-based management models in Islamic higher education. It contributes to the discussion on how faith-based universities can achieve sustainable academic excellence and global relevance without compromising cultural authenticity.